Protection For Tender Participants Businesses That Are Losses Due To Collection According To Business Competition Law - Imam Haryanto; Muthia Sakti; Wirya Agung Kusuma Putra (Universitas Sang Bumi Ruwa Jurai, 2020)
The development of the Indonesian economy is aimed at improving the lives of people who are just and prosperous. This is an ideal that has been mandated in the 1945 Constitution and Pancasila. One of the obstacles in the Indonesian economy is the existence of monopolistic practices and unfair business competition in business or business in Indonesia. Tender conspiracy is one of the forms of action prohibited in the Anti-Monopoly Law because tender conspiracy is fraudulent and detrimental, especially to other tender participants who do not conspire, because automatically in the tender, the winner cannot be regulated, but rather who does it. the best bid is the winner and apart from that bid rigging is an anti-competitive act. Regarding the conspiracy, there is a KPPU Decision relating to this matter, namely the KPPU Decision Case Number 6 / KPPU-L / 2015 regarding the construction of the Barito Kuala Regency DPRD building and its Land Development, in its decision the KPPU Commission Council stated that Reported Party I (PT. Citra Kharisma Persada), reported II (PT. Cempaka Mulia Perkasa), reported III (PT Sumber Nor Abadi), reported IV (Pokja I in the Human Settlements Division of the Public Works Office of Barito Kuala Regency Fiscal Year 2013) was proven legally and convincingly violating Article 22 of the Law Number 5 of 1999. This research will discuss legal protections for business actors participating in tenders who suffer losses due to conspiracy in the KPPU's decision.